Effect of the reverse transcriptase inhibitor efavirenz on 5-azacytidine-induced LINE1 long interspersed repeat expression and genetic instability in acute myeloid leukemia cells - Kh. M. Magomedova; I. A. Antonova; M. S. Strelkov; V. A. Nurtdinova; V. T. Cheshchevik; K. I. Kirsanov; G. A. Belitsky; M. G. Yakubovskaya; O. A. Vlasova (Успехи молекулярной онкологии)
Introduction. The use of hypomethylating agents in the treatment of acute myeloid leukemia has increased overall patient survival by 12 %. However, alongside their potent antitumor effect, hypomethylating agents negatively impact genome stability due to the transposition of activated LINE1 elements, which contributes to the short duration of remission. Since LINE1 retrotransposition requires the ORF2-encoded reverse transcriptase, homologous to the retroviral enzyme, we proposed combining hypomethylating agents with a non-nucleoside inhibitor of this enzyme to reduce the genotoxic effects of 5-azacytidine.Aim. To evaluate the effect of efavirenz on 5-azacytidine in cultured acute myeloid leukemia cells regarding: сytotoxic activity, expression of long interspersed nuclear elements (LINE1), the level of genetic instability.Materials and methods. The study was conducted on THP-1 and KG-1 acute myeloid leukemia cell lines. 5-Azacytidine (hypomethylating agents) and efavirenz (reverse transcriptase inhibitor) were used. Cytotoxicity was assessed via the resazurin assay, apoptosis and necrosis rates were measured by flow cytometry, LINE1 expression was quantified using real-time polymerase chain reaction, and DNA damage was evaluated via the comet assay.Results. Efavirenz did not affect the cytotoxicity of 5-azacytidine. Immunofluorescence staining of LINE1-encoded ORF1 protein and flow cytometry confirmed that efavirenz did not alter LINE1 expression levels. However, comet assay data indicated that combining 5-azacytidine with efavirenz reduced its genotoxic effects.Conclusion. Our findings demonstrate, for the first time, the potential of a novel acute myeloid leukemia treatment strategy combining hypomethylating agents with reverse transcriptase inhibitors.